2013
DOI: 10.1016/j.ijgo.2013.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance after conservative surgical treatment of postpartum hemorrhage

Abstract: Of the 4 procedures, BIL had the least deleterious effect on reproductive performance; SWUD increased the risk of premature ovarian failure, and B-Lynch increased the risks of endometriosis, intrauterine adhesions, placenta previa, and preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some studies have reported that uterine compression sutures do not appear to adversely affect menstrual and fertility outcomes in most women [9,10]. However, one study reported the higher prevalence of infertility after a B-Lynch suture [11]. The cause of infertility was considered to be intrauterine adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that uterine compression sutures do not appear to adversely affect menstrual and fertility outcomes in most women [9,10]. However, one study reported the higher prevalence of infertility after a B-Lynch suture [11]. The cause of infertility was considered to be intrauterine adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, although the numbers of examined cases were still small, obstetric complications of pregnancies occurring after the B-Lynch suture were reported [11]. These authors investigated 30 cases of pregnancies after the B-Lynch suture and reported a higher incidence of abortion, preterm labor, and placenta previa.…”
Section: Discussionmentioning
confidence: 99%
“…12 Uterine instrumentation and number of losses were determined to be the major risk factors. 12 Similarly, the risk of adhesion formation after postpartum cavity instrumentation is reported to be as high as 19-27%, 13,14 with the highest risk occurring between 2 and 4 weeks postpartum. 6 Intrauterine adhesions can also form after uterine instrumentation in nongravid uteri.…”
Section: Epidemiogy and Etiologymentioning
confidence: 99%
“…B-Lynch sutures provide a useful conservative surgical technique avoiding hysterectomy, especially in hospitals without interventional radiology support. The pregnancy rate also seems to be acceptable after the B-Lynch surgical technique (4), but systematic followup data are scarce and based on relatively small study populations (4,5).…”
Section: Sirmentioning
confidence: 99%